The Indian Diaspora as a Social Movement: The Case of the Gulf Countries - Hayati Ünlü (Turkish Journal of Diaspora Studies, 2021)
In this study, the Gulf diaspora of India is examined with a social movement perspective. The aim of the study is to analyze how the Gulf diaspora was rebuilt during the Modi period. Arab countries in the Persian Gulf began to develop as a result of huge oil reserves and needed an intense workforce in the 1970s to have a modern state capacity. The required capacity of migrant workers was supplied from India, the Persian Gulf, and the South Asia axis and became one of the largest migration corridors in the world. Migrant workers have both stimulated the Gulf economies and become the backbone of the Indian economy. On the contrary, in the Modi period, with the new diaspora strategy, diaspora identity was rebuilt similar to a social movement. Political process theory and contentious theory have been used in attempts to analyze the rebuilding of diaspora identity. In recent years, social movement theory has also been used frequently in diaspora studies. In this study, a new model is proposed and the change in India's Gulf diaspora is examined in the context of macro, meso, and micro dynamics. In this context, diasporas as a social movement is first discussed theoretically. Subsequently, the emergence, development, and content of the Indian diaspora in the Gulf region is reviewed historically. In another section, how the diaspora was strategically rebuilt in the Modi era is discussed through the proposed model. In conclusion, the damage to diaspora politics caused by the new Covid-19 pandemic and the rising trends are evaluated.